SYNTHESIS AND PHYSICAL-CHEMICAL PROPERTIES OF WATER-SOLUBLE 3-BENZYLXANTHINE DERIVATIVES - K. V. Аleksandrova; S. V. Levich; O. S. Shkoda; D. M. Yurchenko (Zaporozhye State Medical University, 2015)
Introduction Nowadays, research of novel biological active compounds with low toxicity, are carried out among different classes of organic compounds of natural and synthetic genesis. One of the main ways of these studies is search of water-soluble compounds - convenient objects for pharmacological researches. In recent years researchers paid attention to xanthine derivatives, because of their high variativity of possible chemical modification and ability to form different salts with wide spectrum of biological action. Thus, among water-soluble xanthine derivatives were found compounds with pronounced antioxidant, diuretic and analeptic properties. Primary methods of obtaining water-soluble xanthine derivatives are direct interaction of bases with xanthine molecule or insertion basic or acidic residues in positions 7 or 8 of xanthine bicycle. According from the above, search of biologically active compounds among water-soluble substituted xanthines is prospective and actual. The aim of the study was development of synthetic ways of obtaining novel water-soluble derivatives of 3-benzyl-8-methylxanthine and studying their physical and chemical properties. Material and methods Melting points of obtained compounds were determined by capillary method on PTP (M) device. ІR-spectra of synthesized compounds were recorded on the Bruker Alpha device (company «Bruker» - Germany) on 4000-400 sm-1 with using console ATR (direct insertion of compound). 1Н NMR-spectra were recorded on the Varian Mercury VX-200 device (company «Varian» - USA) solvent - (DMSO-d6), internal standart - ТМС. Elemental analysis was made on Elementar Vario L cube device. Chromatoraphic studies were made on the plates Sorbfil-AFV-UV (company «Sobrpolimer» -Russia). Systhems for chromatography: «acetone-propanol-2» in ratio 2:3, «propanol-2-benzene» in ratio 10:1 and exersized in UV-light in wave 200-300 nm. Results and discussion We developed methodic of synthesis of water-soluble salts of 3-benzyl-8-methylxanthine. Reflux of 3-benzyl-8-methylxanthine 1 with sodium hydrooxide or ammonium hydroxide in the aqueous solution and ethanolamine, diaethylamine or morpholine in the aqueous propanol-2 led to formation of 3-benzyl-8-methylxanthinides-7 2a-e. The next stage of our study was synthesis of 3-benzyl-8-methylxanthinyl-7-acetic acid 3 with the next obtaining of acetates 5a-h. Acid 3 were synthesized by direct interaction of 3-benzyl-8-methylxanthine 1 or xanthinides-7 2a-e with chloroacetic acid and by hydrolysis of its amide 4 or propyl ester 6. Water-soluble 3-benzyl-8-methylxanthinyl-7-acetates 5а-h were obtained by heating acid 3 with primary, secondary and tertiary amines and ammonium in aqueous or aqueous-alcohol solutions. We also developed alternative method of synthesis of propyl 3-benzyl-8-methylxanthinyl-7-acetate 6, by reflux of acid 3 in propanol-1 with catalytic quantity of dioxane and sulfuric acid. Conclusions Methodic of synthesis of novel water-soluble 3-benzyl-8-methylxanthinides-7 has been developed by interaction of 3-benzyl-8-methylxanthine with bases in aqueous or aqueous alcohol solution. We developed universal method of obtaining of 3-benzyl-8-methylxanthilnyl-7-acetic acid, its amide and water-soluble salts. On example of 3-benzyl-8-methylxanthinyl-7-acetic acid we proposed alternative method of synthesis of alkyl esters - convenient objects for next chemical modification. Structure and identity of all synthesized compounds has been proved by elemental analysis, IR-, 1Н NMR-spectroscopy data and by thin layer chromatography.